Evaluation of plant beneficial microbes for bio-hardening of in-vitro raised pomegranate saplings - SINGH, N V; KARWA, N N; BIRAJDAR, S B; PARASHURAM, SHILPA; PATIL, P G; BABU, K D; MUNDEWADIKAR, D M; SANGNURE, VIPUL; GARGADE, V A; SHARMA, JYOTSANA (The Indian Journal of Agricultural Sciences, 2021)
Five beneficial microbial agents either alone or in combinations were used to inoculate one year old in-vitro raised pomegranate plants of cv. Bhagawa for further utilization of these microbes as bio-hardening agents. A pot culture experiment was initiated comprising 15 treatments each having three replications. The growth, physiological and biochemical parameters of the inoculated and control plants were recorded at 90 days after inoculation. Microbes and microbial formulations were evaluated for their further utilization as bio-priming agents in in-vitro raised pomegranate plants. Plants inoculated with Aspergillus niger strain AN27 (Asp) + Penicillium pinophilum registered significant increase in plant height (225.00 cm) and plant spread E-W (198.33 cm) as compared to control. Asp + Pseudomonas fluorescens inoculated plants performed significantly better with respect to total chlorophyll (1.84 mg/g FW), SPAD value (41.23) and total phenol content (0.81 mg/g FW) as compared to non-inoculated plants. Plants inoculated with AMF (Glomus intraradices) + T. viridae and T. harzianum was at par with Asp + P. fluorescens in total chlorophyll content (1.71 mg/g FW) and SPAD value of leaves (36.10). Plants inoculated with AMF in combination with P. pinophilum (T10), P. fluorescens (T11) and T. viridae and T. harzianum (T12) registered higher photosynthesis as compared to control and many other treatments. Microbial treatments were found effective in improving most of the morphological, physiological and biochemical attributes of inoculated pomegranate plants.